ANALISIS EFEKTIVITAS PROGRAM KEMITRAAN DAN BINA LINGKUNGAN PT INDUSTRI KERETA API (INKA) PERSERO PADA UMKM - Anny Widiasmara (INVENTORY: JURNAL AKUNTANSI, 2018)
This research is intended to analyze Partnership and Community Development Program (PKBL) of PT INKA (Persero) at UMKM as one of the program. Corporate Social Responsibility (CSR) and to find out the relationship between the partners of PT INKA (Persero) Partnership and Community Development Program (PKBL). The research was conducted on 50 partners of PT INKA (Persero) located in Madiun Regency. Data Technique uses primary and secondary data. The data were analyzed by descriptive statistic with Likert scale, Importance of Performance Analysis (IPA), and Cross Tabulation Test (Crosstab). The result showed that PT INKA (Persero) Partnership and Community Development Effectiveness Program achieved the program objectives effectively. Based on the result of Cross Tabulation (Crosstab) there is a significant correlation between characteristic of assisted life with coaching program.